2018
DOI: 10.1080/10717544.2018.1494226
|View full text |Cite
|
Sign up to set email alerts
|

Nose-to-brain delivery of temozolomide-loaded PLGA nanoparticles functionalized with anti-EPHA3 for glioblastoma targeting

Abstract: Glioblastoma is the most common malignant brain tumor. Efficient delivery of drugs targeting glioblastomas remains a challenge. Ephrin type-A receptor 3 (EPHA3) tyrosine kinase antibody-modified polylactide-co-glycolide (PLGA) nanoparticles (NPs) were developed to target glioblastoma via nose-to-brain delivery. Anti-EPHA3-modified, TBE-loaded NPs were prepared using an emulsion-solvent evaporation method, showed a sustained in vitro release profile up to 48 h and a mean particle size of 145.9 ± 8.7 nm. The cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(50 citation statements)
references
References 34 publications
0
50
0
Order By: Relevance
“…Many strategies are taken to increase the temozolomide concentration in the CNS, overcoming the boundaries of BBB [64][65][66][67][68]. What was shown earlier, simple implementation of radiotherapy, which is the damaging factor of BBB [69], improves the efficacy of TMZ [70].…”
Section: Discussionmentioning
confidence: 99%
“…Many strategies are taken to increase the temozolomide concentration in the CNS, overcoming the boundaries of BBB [64][65][66][67][68]. What was shown earlier, simple implementation of radiotherapy, which is the damaging factor of BBB [69], improves the efficacy of TMZ [70].…”
Section: Discussionmentioning
confidence: 99%
“…The nanocarrier was functionalized with a tyrosine kinase antibody, EPHA3 (ephrin type-A receptor 3) which effectively target the drug-loaded nanocarrier to the glioblastoma in the brain, The results show 1.3 fold prolonged release and significantly higher brain concentration. 128 However, all the studies are performed on the animal models, ie, still in the preclinical stage, which suggested the need of a lot of further clinical studies on human volunteers to establish its applicability in real patients.…”
Section: Quantum Dotsmentioning
confidence: 99%
“…Anti-EPHA3 functionalized nanoparticles increased the median animal survival by 1.37-fold compared to non-targeted nanoparticles. Overall, the author concluded that anti-EPHA3 modified PLGA nanoparticles might potentially serve as a nose-to-brain drug carrier for the treatment of GBM [120].…”
Section: Drug Delivery Systems For Nose-to-brain Delivery In Glioblasmentioning
confidence: 99%
“…Ephrin type-A receptor 3 (EPHA3) is a membrane-associated receptor overexpressed in the stroma and vasculature of gliomas[153]. Chu and co-authors developed PLGA nanoparticles functionalized with anti-EPHA3 antibodies for direct nose-to-brain delivery of temozolomide butyl ester (TBE)[120]. Nanoparticles loaded with TMZ were prepared by emulsion-solvent evaporation method and subsequently coated with N-trimethylated chitosan (TMC) and their surface functionalized with anti-EPHA3 antibodies.The drug release studies showed a sustained release of TMZ from the nanoparticles up to 48 h. The results of a cytotoxicity assay on C6 cells and of nanoparticles cellular uptake demonstrated that the anti-EPHA3 functionalization could enhance GBM targeting increasing the cytotoxic effect of the drug.…”
mentioning
confidence: 99%